(untitled) (Law, State and Telecommunications Review, 2024)
[Purpose] This paper seeks to develop, from the current doctrine and regulations, some guidelines for the debate that the Law will have to give shortly, about a new type of personality and its attributes those humanoid robots that are capable of questioning their initial programming and take actions on your own. [Methodology] It is a work developed through a legal-hermeneutical and documentary analysis methodology. The authors used legal doctrine as sources, especially books and book chapters, research results, as well as articles in scientific journals evaluated by peers and indexed in legal databases. To develop the objective of the paper, the authors outlined several stages, first, the search and recovery of information, second a critical analysis, and finally the interpretation of all of the above. [Findings] The authors present their results, on the one hand, with an analysis of the personality of humanoid robots, and on the other, with some reflections on their attributes. The paper presents a critical study on the legal situation of the regulation of the autonomy of the will; which must be understood as the materialized faculty of self-determination that these robots could have in making their own decisions and concerning the rights, obligations, and responsibilities that the Law decides to recognize. All of the above, from artificial intelligence systems that are not subordinated to their initial programming, or the immediate and permanent control of a natural person.